Subject Guides in Academic Libraries: A User-centered Study of Uses and Perceptions - Ouellette, Dana (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper reports on the results of an ongoing user-centered research project investigating student use and perception of subject guides in academic libraries. Preliminary results suggest that although students rarely use subject guides, they might if subject guides were specifically optimized for the way students actually use them. Cet article présente les résultats d’une étude en cours sur l’utilisation des guides thématiques par les étudiants et les perceptions qu’ils en ont, dans les bibliothèques universitaires. Les résultats préliminaires suggèrent que malgré une utilisation plutôt rare, les étudiants les utiliseraient davantage si les guides thématiques étaient adaptés à l’utilisation réelle qu’ils en font. ***Full paper in the Canadian Journal of Information and Library Science***